2009
DOI: 10.1038/sj.bjc.6605068
|View full text |Cite
|
Sign up to set email alerts
|

Alternative implication of CXCR4 in JAK2/STAT3 activation in small cell lung cancer

Abstract: Small cell lung cancer (SCLC) is an aggressive, rapidly metastasising tumour. Previously, we demonstrated the influence of CXCL12 -CXCR4 interaction on processes involved in metastasis and chemoresistance in SCLC. We show here that STAT3 is expressed in both primary SCLC tumour tissues and SCLC cell lines. We investigated the function of STAT3 upon CXCL12 stimulation in SCLC cell lines. Small cell lung cancer cell lines present constitutive phosphorylation of STAT3, and in the reference cell lines NCI-H69 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 40 publications
4
34
0
Order By: Relevance
“…Of note, CXCR4 contains two domains involved in Jak2/STAT3 signaling and binding of SDF-1 to CXCR4 is able to trigger STAT3 activation (2). SDF-1-increased phosphorylation of STAT3 has been observed to facilitate growth and spread of small cell lung cancer (20). In addition, SDF-1 has been shown to protect chronic lymphocytic leukemia B cells from apoptosis through upregulated STAT3 activation (6).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Of note, CXCR4 contains two domains involved in Jak2/STAT3 signaling and binding of SDF-1 to CXCR4 is able to trigger STAT3 activation (2). SDF-1-increased phosphorylation of STAT3 has been observed to facilitate growth and spread of small cell lung cancer (20). In addition, SDF-1 has been shown to protect chronic lymphocytic leukemia B cells from apoptosis through upregulated STAT3 activation (6).…”
Section: Discussionmentioning
confidence: 96%
“…By binding to CXCR4, SDF-1 has been reported to activate a series of downstream signaling pathways. SDF-1/CXCR4-triggered signal transducer and activator of transcription 3 (STAT3) activation is one of critical pathways that has been shown to facilitate cell growth, inhibit apoptosis, and mediate migration of mesenchymal stem cells (6,10,20). Of note, it is well documented that STAT3 activation plays a cardioprotective role following myocardial I/R injury.…”
mentioning
confidence: 99%
“…SCLC cells expressed high levels of CXCR4 responsible for cell migration and adhesion, growth signals, or resistance to drugs [51]. Constitutive phosphorylation of STAT3 occurred in SCLC cells and could be further accelerated by CXCL12 stimulation through interactions between CXCR4 and JAK2 in SCLC cells [52]. CXCR4 antagonists could inhibit CXCR4-mediated SCLC cell adhesion and growth and increase SCLC cell sensitivity to cytotoxic drugs [51], as an independent predictor of a favorable prognosis in patients with lung adenocarcinoma [53].…”
Section: Roles Of Chemokines In Cancer-related Inflammationmentioning
confidence: 98%
“…Previous studies have shown that CXCR4 activation affects proliferation and migration through extracellular signal-related kinase (ERK) and AKT phosphorylation, 30,31 c-SRC phosphorylation 32,33 and the Janus Kinase/signal transducer and activator of transcription 3 (JAK/STAT3) pathway. 34,35 Moreover, CXCL12 treatment can induce the phosphorylation of focal adhesion kinase (FAK) regulating cell flexibility and migration. 36 To evaluate the HDI effect on CXCR4 function, the phosphorylation status of ERK1 and 2, c-SRC, FAK and STAT3 was evaluated following HDI treatment.…”
Section: Discussionmentioning
confidence: 99%